1996
DOI: 10.3109/00016349609047102
|View full text |Cite
|
Sign up to set email alerts
|

Primary cancer of the fallopian tube

Abstract: Fallopian tube cancer is a treatable disease but cure can be only achieved in patients with early tumor. Postoperative radiotherapy may result in better local control but does not preclude extrapelvic dissemination, therefore adjuvant chemotherapy should be considered in high risk patients. Registration of all new cases as well as prospective multicenter studies are warranted to establish optimal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
3
11
1
Order By: Relevance
“…Well-differentiated tumours were observed in 8%, while 32% had grade 2 and 58% grade 3 tumours, which is in concordance with earlier studies [4] . The distribution of histological subgroups is also comparable with that in earlier studies [29,30] , with 80% serous adenocarcinomas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Well-differentiated tumours were observed in 8%, while 32% had grade 2 and 58% grade 3 tumours, which is in concordance with earlier studies [4] . The distribution of histological subgroups is also comparable with that in earlier studies [29,30] , with 80% serous adenocarcinomas.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of 61 years of the patients in the present series is similar, while the stage distribution was somewhat different from that reported in other studies [1,3,9] ; only 10% of our patients had stage I disease as compared to 20-42% in earlier studies [3,4,26] . Well-differentiated tumours were observed in 8%, while 32% had grade 2 and 58% grade 3 tumours, which is in concordance with earlier studies [4] .…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Patients with no detectable residual tumor had a 60% 5-year survival rate, but no patient with residual disease was alive at 5 years. This is in accordance with previous reports and stresses the need for radical surgery with maximum debulking (13)(14)(15)(16) . However, whether the poor outcome in patients who had residual tumor left after cytoreductive surgery is due to incomplete surgery or to tumor biology cannot be answered by this study.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the low prevalence of the disease and heterogeneous postoperative regimens, it is difficult to establish therapeutic guidelines. While some authors favor postoperative chemotherapy like in ovarian cancer, other studies have recommended postoperative radiation covering the para-aortic lymph nodes [6][7][8][9][10][11][12][27][28][29]. In an early evaluation of our patients, Klein et al [30] showed an improvement of prognosis by postoperative radiation in 24 patients compared to 49 women who underwent adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 95%